Práticas gerenciais de Programas de pós-graduação stricto sensu na UFLA - Pinto, Deila Pereira (2018)
This study was conducted with the objective of comparatively analyzing the management practices of two older Stricto sensu Graduate Programs of the Universidade Federal de Lavras (UFLA), one with concept 7 (Soil Science) and another with concept 5 (Administration), under the perspective of Public Administration paradigms, and considering the three dimensions of public administration analysis: socio-political, institutional-administrative, and economic and financial. This is a research of theoretical and empirical character. We surveyed secondary data of a documentary and bibliographical nature and collected field data through semi-structured interviews and the application of a closed questionnaire with the program coordinators. The research is essentially qualitative for exploring the interpretation of social actors (former and current coordinators). The results demonstrate that the Graduate Program in Soil Science has a hybrid management model, predominantly using the Management Paradigm. It is considered managerial in terms of strategies since the program is more concerned with results (maintaining concept 7), work processes, given that it is not fixed around the rules and procedures, and efficiency of the administrative processes. The Graduate Program in Administration also has a hybrid management model, with a predominance of the Bureaucratic Paradigm moving towards the managerial model. The program showed traces of Patrimonial Management in the early decade of the program, in which friendship relationships were important for the good performance of the activities necessary for the success of the program. However, it presented personalist characteristics in more recent administrations. The result of this comparison served to assess the management conditions of the programs, which may favor the management of other programs at UFLA, to obtain better results.